Women and weight loss - Anderson, Nicki; Monterey Bay Video Production Company; IDEA Health & Fitness Association (Monterey, CA : Monterey Bay Video Production Company, 2006)
Program for women that teaches them how to sty focused on their health, while addressing their concerns about their weight and more importantly, helping them to be successful with their weight management efforts
Title from title screen
Presenter : Nicki Anderson
Keywords: Physical fitness for women; Women -- Health and hygiene; Women -- Nutrition; Diet